Konsep Kepimpinan Berteraskan Islam umar Al-khattab RA - Simangunsong, Suwandi (2024)
Umar Al-khattab RA was the second khalifat who did a lot of new ijtihad along with the change of time, the expansion of the territory and the state of his government. The ijtihads in his leadership had a great impact on the progress of his government. Based on this positive perspective, what can be emulated from the leadership of Umar Al-khattab RA to build the concept of leadership based on Islam? How did Umar Al-khattab RA carry out his leadership, so that the people can accept his concept of Islamic leadership? Based on those questions, this study will explain three objectives. First, identify the concept of leadership based on Islam Umar Al-khattab RA.